Capabilities for Ehealth Education : Developing Undergraduate Digital Literacies for Health Professionals : Final Report. - Kenny, Amanda; Iacono, Teresa; McKinstry, Carol; Hannon, John; Knight, Kaye; Whitrow, David (Office for Learning and Teaching, 2016)
The emergence of ehealth systems creates significant pressure on universities to ensure graduates have the capability to join a workforce responsive to widespread change. Information and communication technologies are rapidly re-shaping work environments and clinical practice, with a shift to national systems of health and clinical informatics that enables practices that cross professional and geographic boundaries. There is evidence that graduates from undergraduate health education programs are currently not well prepared to work within an eHealth system. Addressing this deficit is urgently required to ensure graduate work readiness. This project built capabilities through eHealth education that will prepare graduates for the networked informatics of healthcare. The practice needs of graduates in digitally networked inter-professional health contexts was investigated, drawing on the recommendations of a recent OLT report on eHealth education. Curriculum focused on digital literacies needed by health graduates for contemporary healthcare will be developed.